Edukasi 3M Melalui Media Games Sebagai Tindakan Preventif Penularan Covid-19 Pada Anak Panti Asuhan Rodhatul Jannah Kota Tarakan - Fitriya Handayani; Alfianur; Nurman Hidaya; Maria Imaculata Ose; Gusriani (Idea Pengabdian Masyarakat, 2021)
Covid-19 is still a hot topic of discussion. Many things have been attempted by the government to combat this. But apart from that, there are more important things that should be the basis for fighting COVID-19, namely knowledge about the Covid-19 pandemic, especially for children. If someone already has knowledge about the COVID- 19 pandemic they are currently facing, then each individual will naturally take action to prevent COVID-19. This lack of knowledge is a problem at the Rodhatul Jannah Orphanage in Tarakan City, so it is important to hold education. The service method is by Lectures/counseling, Discussions and questions and answers through snakes and ladders game. The result of this activity is that the orphans who receive education are very enthusiastic and active in counseling based on snakes and ladders games so that they are committed to always implementing the Covid-19 prevention protocol. From these results it can be concluded that media games are very effective in providing education to children.